The Effect of Flash Sale on Purchasing Decisions: A Theoretical Approach - Andriyana, Ahmad Saoki; Suparno, Suparno; Wibowo, Agus (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The current research was explored to analyze the Effect of Flash Sale on Purchasing Decisions on E-commerce. By applying a qualitative method, this research carried out to explore the prepositions of promotion study and conceptualized flash sale promotion as a promotional tool. The data collection technique applied a literature survey. The literature survey outlined some of the findings of previous researchers’ references and elaborated the study using grounded theory. This research, methodically, was expected to be able to explain flash sales, and purchasing decisions. The findings proved that Flash Sale promotions had a positive and significant influence on purchasing decisions, and encouraged impulse buying behavior on various platforms, such as Shopee and Lazada. Flash Sales provided attractive price reductions for consumers, encouraging them to make purchasing decisions. The results also showed that promotional strategies such as Flash Sale and Free Shipping offers promoted a positive impact on increasing product sales and influencing consumer purchasing decisions. Keywords: Discount, Flash Sale, Purchasing Decision